Risk factors for and incidence of osteoporosis in patients with breast cancer by gender : a nationwide cohort study - Jin Ah Lee; Hye Sun Lee; Soyoung Jeon; Dooreh Kim; YoungJoo Lee; SooYun Bae; Woo-Chan Park; Chang Ik Yoon (Scientific Reports)
Abstract Osteoporosis is common in breast cancer patients, but gender-specific research on its incidence and risk factors is limited. This study examined the incidence and risk of osteoporosis in male and female breast cancer patients and analyzed the risk factors for fractures. This nationwide retrospective cohort study used data from the Korean National Insurance database, identifying invasive breast cancer patients from January 2009 to December 2015.Overall, 80,661 participants (299 males ; 80,362 females) were included. Matching was performed at a 1:5 ratio, based on age, treatment modalities and Charlson Comorbidity Index scores [CCI], resulting in 294 males and 1,470 females.Before and after matching, females consistently showed higher osteoporosis prevalence than males (16.7% vs. 5.0% before, 27.6% vs. 4.8% after, p < 0.001). Before matching, hip or vertebral fractures incidence showed no difference (1.2% vs. 1.3%, p = 0.789), but after matching, a significant difference was observed. (4.0% vs. 1.0%, p = 0.011). Endocrine therapy increased osteoporosis risk, particularly among females (hazard ratio [HR], 6.37; 95% confidence interval [CI], 3.74–10.89; p < 0.001). Age, steroid use, and CCI score were significant risk factors for osteoporosis. Adjusting for other variables, females with osteoporosis had a higher hip or vertebral fracture risk than males (HR, 3.96; 95% CI, 1.24–12.64; p = 0.020). Our study highlights gender-specific risks for osteoporosis and fractures in breast cancer patients, contributing to a comprehensive understanding for improving long-term outcomes and quality of life in survivors.